Hydrographic GIS - Hecht, Horst (The International Hydrographic Review, 2025)
This manuscript is a reprint of the original paper previously published in 2000 in The International Hydrographic Review (IHR, https://ihr.iho.int/): Hecht, H. (2000). Hydrographic GIS. The International Hydrographic Review, 1(2), new series, 71–76. https://journals.lib.unb.ca/index.php/ihr/article/view/20499/23662